Development of Student Worksheets on Heat Material Based on Guided Inquiry to Increase Creative Thinking Skills - Lusiana Shinta Dewi; I Dewa Putu Nyeneng; Wayan Suana (Kasuari: Physics Education Journal (KPEJ), 2019)
The aim of this research  were to develop and determine the attractiveness, convenience, usefulness, effectiveness of student worksheets based on guided inquiry on heat material. The research development method used in this study refers to the method development by Sugiyono, namely: Potential and problem analysis, Information collection, Product Design, Design validation, Design revision, Product testing, Product revision, Usage trial, Product revision, Mass production. This step was started by conducting questionnaire filling addressed to the  science teachers and students of VII class at SMP Negeri 1 Bandar Sribhawono. The product’s design validation evaluation was conducted by the design experts and content / learning material experts. Furthermore, product trial were conducted on 7 students using one by one test, that states this product has excellent quality of attractiveness, the quality of convenience is very good, and the quality of usefulness is good.The usage trial was conducted in one sample class consisting of 34 VII students in SMP Negeri 1 Bandar Sribhawono.The results of testing the attractiveness got an average score of 3.19 in the attractive category, the convenience got an average score 3,20 in the convenience category, and the usefulness got an average score 3,38 in the very usefulness category. The result obtained from the use of this trial is the post-test score, so that the percentage of students' mastery of learning fulfilled the Minimum Passing Grade by 85%. Based on this analysis, the worksheets developed can be used effectively in the learning process.